Capitalizing on Gen Z students' interests and motivations to develop Global Citizenship Education in VEs - Mariadelaluz Matus-Mendoza (University of Groningen Press, 2023)
The article reports on the outcomes yielded by two different virtual exchanges conducted before and after the forced closures of academic institutions due to the COVID-19 pandemic in 2020. They were designed considering interests and motivations of Gen Z students (Seemiller & Grace, 2016) and aimed at including a Global Citizenship Education approach to deal with contemporary world challenges. The current article details these telecollaborations between two cohorts of a large private research university in Eastern North America and two large research state universities in the Southern part of North America and Western South America that were brought together to deepen their understanding on the migration phenomenon by performing collaborative tasks. Throughout these exchanges and at the conclusion of the courses, students reported common and divergent perspectives on issues discussed. Although there were more points of coincidence in their understanding of the phenomenon, when learners did not agree, they sought to see the other's perspectives and strived to find common ground. Overall, the evaluation of these virtual exchanges was considered a beneficial and rewarding experience that not only made their learning easier but gave access to more global perspectives about the migration phenomenon. The terms virtual exchange and telecollaboration are treated synonymously.